Post-surgical Thyroid Bed Pyoderma Gangrenosum Mimicking Recurrent Papillary Thyroid Carcinoma - Dolci, Alessia; Indirli, Rita; Genovese, Giovanni; Derlino, Federica; Arosio, Maura; Marzano, Angelo Valerio (Frontiers in Endocrinology, 2019)
Background: Pyoderma gangrenosum (PG) is a rare inflammatory disease presenting with chronic-recurrent cutaneous ulcers histopathologically hallmarked by neutrophilic infiltrates, which may occur more frequently at sites of surgical traumas. The disease is habitually limited to the skin, but it can virtually involve any organ. Nevertheless, no prior cases of PG involving the thyroid bed have ever been reported. Case Report: A bilateral PG of the breast was diagnosed in a 51-year-old woman and treated with intravenous methylprednisolone pulse-therapy and cyclosporine, with partial improvement. During the hospitalization, cytological examination of two hypoechoic thyroid nodules by fine-needle aspiration (FNA) was consistent with thyroid carcinoma. After total thyroidectomy, histopathology confirmed a papillary thyroid cancer (PTC), and radioactive iodine ablation was performed. At 12-month ultrasonographic follow-up, two hypoechoic avascular areas localized in the empty thyroid bed raised the suspect of PTC recurrence. However, (i) undetectable levels of thyroglobulin without anti-thyroglobulin antibodies, (ii) neutrophilia and increased inflammatory marker levels, and (iii) cytological examination of FNA showing numerous neutrophils induced to suspect thyroid bed PG infiltration. An ex juvantibus approach with high-dose methylprednisolone led to dimensional reduction of the hypoechoic areas on ultrasonography, thus confirming the hypothesis of thyroid bed PG. Conclusion: This case of thyroid bed PG supports the idea that PG reflects a cutaneous phenotype encompassed in the spectrum of systemic neutrophilic diseases. Endocrinologists should be aware that thyroid bed PG involvement is an albeit rare differential diagnosis to consider in patients who had undergone thyroid surgery, especially with a history of PG.